Prediction of corroded reinforced concrete slab during chloride-induced corrosion process using corrosion-induced crack widths - Kim, Jing Zhe (Nanyang Technological University, 2023)
Corrosion is a common occurrence in many aspects of the living world today. It is especially evident in the case of reinforced concrete (RC) structures and should not be overlooked the given potential hazards. Thus, more research should be conducted to obtain better understanding on the effect of corrosion of RC structures. Due to the limitation of corrosion testing on existing actual structures, this project aimed to simulate the corrosion process in a controlled chloride environment through accelerated corrosion tests on three RC slabs with application of an impressed current method. The collected data through visual observations is used to analyse the relations between the crack width and reinforcement cross-section loss. The results can be applied on various models of prediction against time and ultimate capacity of the corroded slabs, for the construction of safer structures in the future.